Faith Seeking Understanding: An Introduction to Christian Theology - Chethimattam, John B (Journal of Dharma, 2020)
Daniel L. Migliore, Faith Seeking Understanding, An Introduction to Christian Theology. Grand Rapids, Mich.: William B. Erdmans, 1991, pp. xiii+302, 18.95